Redução de danos em um CAPS AD: discursos de profissionais de saúde - Moreira, Thaís Diniz Santos (2016)
Caring for people with drugs problems historically was based on isolation and moral adjustment. In the 20th century, first harm reduction strategies appears as a measure to decrease risks and damage related to abuse use of psychoactive substances. Ministry of Health politics for Integral Attention to Alcohol and other drugs Users introduce as guiding principles: universality, integrality, equity, expanded clinic, crosscutting, deinstitutionalization and harm reduction. This study aims to analyze speeches of health professionals from Center of Psychosocial Attention Alcohol and Drugs (CAPS AD) about Harm reduction. A case study was carried out with nine CAPS AD health professionals. A semi structured interview was used, a systematic observation and a method of speech analysis. Results showed that work organization mode by the multidisciplinary team affects drug user access, reception process and treatment adherence. User control over drug use shows in the participant’s speech as a matter of willpower, presenting shared elements between common sense, especially the conception that treatment depends on the user wish and willpower, supporting the idea that user is designed as the single responsible for the treatment success. The discourse of the professionals evidenced their views on Harm reduction approach, with meanings that are far to advocating the policy, reducing the approach to prevention strategies and minimization of the aggravations related to the management of inputs and forms of use of the substances. Shows up the difficulties of some participants to defines the approach and describe its operationalization, which is added to the statements that refer the absence of their practice in the service, on this is concluded that Harm reduction is not the predominant model of attention in the service. The results also demonstrated that in the speeches of professionals are present elements that reiterate negative stereotypes about drug users and, although socially shared, reverberates negatively in the professional's view. Considering the participation of all professionals in many ways of training, questions about the ideological dimension that interferes in the process of implementation of the Harm reduction, such as the notion that treatment success depends solely on the user, non-tolerance to any form of substance use, and the resistance to own approach. It is therefore necessary investments in activities that had improve learning about alcohol and other drugs, strengthening the aspects of Harm reduction and its operationalization, reverberating in the practices and at the look of the professionals on the drug users and, consequently, in the transformation of the health situation of people with problems related to drug use and abuse.